Development of Embedded Web Server Based on DAC System Using ARM for Industrial Applications. - Kamaraju, Maddu; Gopinath, D. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The scope of networked embedded systems is rapidly increasing day by day due to their demand for monitoring and controlling appliances in home as well as industry. Embedded systems with networking provides web access for the industrial and research centers optimization. Data acquisition system with web access combindly gives the easy implementation of the system which uses ARM processor for control purpose and GPRS technology along with GSM is used for communication around the world. The real time operating system plays a crucial role in the system where the embedded device is booted with ÂµC/OS, which is commonly used RTOS for hard real time systems. The proposed system consists of an ÂµCOS configured for real time scheduling in industrial applications which eliminates the need for server maintenance. This system enhances security by remotely monitoring various appliances.